Minimal Conditions for the Survival of the Euro - Barry Eichengreen; Charles Wyplosz (Intereconomics, 2016)
Most technocrats argue that creating the euro was a way of forcing the pace of political integration, since monetary union is not possible without political union. We disagree and instead put forward four minimal conditions for the survival of the euro. Political integration in Europe has its limits; the trick is to understand when less is more.
Keywords: 330; Währungsunion; Währungsumstellung; Euro